1985
DOI: 10.1088/0741-3335/27/4/005
|View full text |Cite
|
Sign up to set email alerts
|

On the excitation of linear and nonlinear ion-acoustic waves in a double plasma machine

Abstract: In this paper, a mechanism for the excitation of linear and nonlinear ion-acoustic waves in a double plasma machine is suggested. A compressive ion density perturbation is interpreted in terms of "klystron bunching" and a rarefactive ion density perturbation is interpreted in terms of a self-similar expansion. Experimental results support the theoretical model proposed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…3, which is almost equal to the ion-acoustic velocity as observed in a conventional DP device. 2,3 Other characteristics of excited waves will be described in the next section.…”
Section: B Excitation Of Solitary Waves By Applying External Pulsesmentioning
confidence: 99%
See 1 more Smart Citation
“…3, which is almost equal to the ion-acoustic velocity as observed in a conventional DP device. 2,3 Other characteristics of excited waves will be described in the next section.…”
Section: B Excitation Of Solitary Waves By Applying External Pulsesmentioning
confidence: 99%
“…From these works, the DP device is now known to be very useful for the study of particularly nonlinear phenomena in plasmas. The mechanism of wave excitation in the DP device was experimentally clarified by Honzawa 2 and Tsikis et al 3 We intend here to introduce a modified double plasma ͑MDP͒ device and want to emphasize its usefulness for basic plasma wave experiments. The MDP device is similar to the DP device, but it includes a discharge plasma only on the ''target'' plasma side and no discharge on the other side.…”
Section: Introductionmentioning
confidence: 99%
“…In this experiment we studied the effect of such fast beam ions on the wave excitation. In usual cases when pulses with moderate heights below kT e /eӍ2 V are applied, the mechanism of wave excitation has already been well studied by Honzawa 11 and Tsikis et al 12 According to the results of these works, the bunching of pulsed slow beam ions, generated by the applied moderate ramp pulse, forms the prototype of a soliton at an early stage. Here, velocities of these slow beam ions should not be much higher than the ion-acoustic one.…”
Section: A Limitation Of Soliton Amplitudes By Fast Beam Ionsmentioning
confidence: 99%
“…This is because the application of a ramp pulse does not disturb the plasmas so much as the vacuum spark in the former method. By the way, the mechanism of the soliton or shock excitation in the DP-device has been experimentally clarified by Honzawa 11 and Tsikis et al 12 Moreover, Honzawa et al 13 showed experimentally using a technique of double-soliton excitation that a strong interaction between ion-acoustic solitons and resonant beam ions coming from behind resulted in the remarkable amplification of the solitons. In spite of all the works on the ion-acoustic solitons or shocks described above, a question why there exists the limitation in amplitude of ion-acoustic solitons or shocks formed in the grid-or DP-excitation has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The Kadomtsev-Petviashvili (KP) equation was one of the first model equations proposed for higher dimensional ocean pattern [2]. It was first proposed to study the transverse instability of the KdV solitary wave [3].…”
Section: Introductionmentioning
confidence: 99%